(untitled) (Stavební obzor - Civil Engineering Journal, 2024)
This study investigates the influence of various factors on the seismic behavior of geogrid-reinforced soil walls. The research involves modifying soil properties like friction angle, cohesion, elastic modulus, and Poisson’s ratio. The aim is to comprehend the consequent effects on the wall’s horizontal and vertical deformations, the lateral pressure applied to the wall’s surface, and the peak tensile force encountered by the reinforcements under seismic conditions with a maximum acceleration of 0.3g. The primary goal is to enhance the seismic performance of such walls and analogous scenarios. To attain this goal, a two-dimensional numerical analysis is performed employing the finite difference method and FLAC software while accounting for strain considerations. The analysis findings reveal that increasing cohesion at the wall’s height results in a nearly consistent peak tensile force on the reinforcements. However, the impact of cohesion on this force diminishes for wall heights exceeding 4 meters. Elevating the internal friction angle leads to a reduction in the peak tensile force on the reinforcements, particularly in the lower segment of the wall. Conversely, with increasing wall height, the decrease in horizontal pressure on the wall’s rear surface becomes less noticeable, eventually stabilizing at around 1 kilopascal in the upper half of the wall. Altering the soil’s elastic modulus demonstrates that once the value surpasses 35 MPa, the peak tensile force on the reinforcements remains stable, exhibiting no further alterations.